Comparative Analysis of Islamic Higher Education Curriculum and Educational Outcomes in Indonesia and Malaysia: A Systematic Literature Review - I. M. Fatimah Zahro; Muhammad Sirozi (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2026)
This study compares the curriculum characteristics and educational outcomes of Islamic Higher Education Institutions (IHEIs) in Indonesia and Malaysia through a Systematic Literature Review following the PRISMA 2020 guidelines. Literature was collected from Scopus, Web of Science, Dimensions, Crossref, DOAJ, Google Scholar, and Garuda, resulting in 48 eligible studies published between 2015 and 2025. The findings reveal that Indonesian IHEIs generally adopt a decentralized and flexible curriculum emphasizing interdisciplinary integration between Islamic and contemporary sciences, whereas Malaysian IHEIs implement a more centralized curriculum grounded in the Islamization of knowledge and national quality assurance. These differences shape knowledge integration, curriculum governance, graduate competencies, and institutional responsiveness to globalization. The review further demonstrates that curriculum philosophy and governance are key determinants of educational outcomes. Rather than identifying a superior model, this study highlights the complementary strengths of both systems and recommends balancing institutional innovation, quality assurance, global competitiveness, and Islamic educational values in future curriculum development.